PROGRAM EARLY AGROEDUCATION PADA SISWA SEKOLAH DASAR UNTUK MEWUJUDKAN PROGRAM SUSTAINABLE AGRICULTURE - Nancy Oktyajati; Srie Juli Rachmawatie (Universitas Sebelas Maret, 2020)
The early agro education program is one of the agricultural lessons for children from an early age. This community service program was attended by first-grade students of Madrasah Ibtida'iyah (MI) Hidayatul Insan. The community service program begins with a discussion with the teacher to formulate a local content curriculum for agro schooling that will be applied at MI Hidayatul Insan. The next program is the preparation of educational facilities and infrastructure for first-grade students, then providing training to children in gardening or planting starting from nurseries, cultivating land in small pots, and training to care for plants. The purpose of this community service activity is to open up the knowledge of elementary school-age children about agriculture so that their love for agriculture will emerge. The output of community service with this early agro education program is that the Faculty of Science and Agriculture, Islamic University of Batik (UNIBA) Surakarta contributes to its scientific fields, namely engineering, science, and agriculture to support government programs, namely sustainable agriculture. The early agro education program through agro schooling produces four basic competencies that students have, namely students' understanding of plant types, students understanding how plants can grow, understanding the germination process, and students getting to know plants in the Al-Qur'an.Keywords: agriculture, agro schooling, early agro education, sustainable agriculture